Frequency Reconfigurable Fractal Microstrip Filtering Antenna for Cognitive Radio Applications (International Journal of Engineering and Computer Science, 2025)
Tunable microstrip filtering antennas can be used to modify the operating frequency, polarization, or radiation pattern in real time. These antennas provide a number of advantages, such as more flexibility and adaptability and decreased dimensions, weight, and power consumption. The main aim of the current work is to design a tunable microstrip filtering antenna for cognitive radio applications. Prior to tune the frequency of the proposed design the operating bandwidth is enhanced by implementing the Snow-flake Koch fractal optimization of 3rd iteration along with the defected ground structure. To achieve the frequency tunable characteristics a stepped impedance resonator (SIR) filter is integrated with the feed line. The order of the SIR filter is responsible for frequency tunability. At each stage the simulated designs are fabricated and measured using VNA and anechoic chamber. The peak gain achieved is 3.2dBi whereas the minimum gain achieved is 1.7dBi. The co-polarization values are 25dB is stronger than cross-polarization values. There is a good concurrence is observed between the simulated and measured results in terms of 10dB Return Loss, VSWR, Gain, Directivity and Far Filed radiation patterns. The proposed design is well suited for cognitive radio applications as it is operating at 1.97GHz, 3.97GHz and 5.87 GHz frequencies respectively.